From Valsartan to Ranitidine: The Story of Nitrosamines So Far - Iram, Mahvash (Indian Journal of Pharmacy Practice)
Every point in the process of caregiving contains a certain degree of inherent unsafety! The very idea of patient safety is the prevention of adverse effects to patients associated with health care. While healthcare has become more effective, it has also become more complex with extensive use of new technologies, medicines and treatments.